The role of user charges for infrastructure maintenance costs - Kudláčková, Nina (Univerzita Pardubice, 2010)
The increasing importance of maintenance has led to research questions on ways of charging infrastructure users and mobilisation of funds for maintenance activities. Technological developments help to bring advanced and differentiated schemes of infrastructure charging closer. For long distance transport, charging road use in one country may well lead to changes in competitive positions of countries. The system of road user charges introduced in one country might change the competitive positron of the neighbouring country. The other dimension of competition is between various transport modes. Depending on the various origin-destination submarkets, there may be substantial competition between transport modes. This calls for an integrated approach to infrastructure Charles in order to ovoid equity problems. This article focuses on these problems from the European point of view.
Keywords: transport user; transport user charges; infrastructure maintenance costs